2016
DOI: 10.2298/hemind150119014g
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Mo alloy coatings as cathodes in chlorate production process

Abstract: The aim of this study was to gain a better understanding of the feasibility of partial replacement of dichromate, Cr(VI), with phosphate buffer, focusing on the cathode reaction selectivity for hydrogen evolution on mild steel and Fe-Mo cathodes in undivided cell for chlorate production. To evaluate the ability of phosphate and Cr(VI) additions to hinder hypochlorite and chlorate reduction, overall current efficiency (CE) measurements in laboratory cell for chlorate production on stationary electrodes were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…containing chromium (Cr-MoO 2 ) electrodes were tested as cathodes for the electrochemical reduction of hypochlorite in neutral and slightly alkaline solutions, respectively [93,94]. In both cases, an increased activity towards the HER was found with the electrodes of optimized composition as compared to mild steel cathodes.…”
Section: Molybdenum Containing Electrodes and Coatings Fe-mo Alloys mentioning
confidence: 99%
See 1 more Smart Citation
“…containing chromium (Cr-MoO 2 ) electrodes were tested as cathodes for the electrochemical reduction of hypochlorite in neutral and slightly alkaline solutions, respectively [93,94]. In both cases, an increased activity towards the HER was found with the electrodes of optimized composition as compared to mild steel cathodes.…”
Section: Molybdenum Containing Electrodes and Coatings Fe-mo Alloys mentioning
confidence: 99%
“…The applicability of phosphate buffer has been studied [42,66,94]. These studies concluded, that in a membrane separated electrochemical cell the cathode current efficiency is slightly increased.…”
Section: The Use Of Alternative Buffers In the Chlorate Processmentioning
confidence: 99%